The impact of YouGlish on English speaking competency in higher education - Miliam Quispe-Vargas; Kevin Mario Laura-De La Cruz; Fabiola Talavera-Mendoza; Gabriela Manzur-Vera; Gerber Pérez-Postigo; Osbaldo Turpo-Gebera; Rocio Diaz-Zavala (OmniaScience, 2024)
Globalization and the information and knowledge age in which we find ourselves demands that Higher Education develops English speaking competency in their students to respond adequately to academic and labor challenges, taking advantage of the virtues of the variety of resources offered by technology. YouGlish is an online oral dictionary whose characteristics can be leveraged for the development of English-speaking competency. This study aims to determine the impact of the use of YouGlish on English speaking competency on their sub-skills of fluency, grammatical adequacy, pronunciation, communicative interaction, and vocabulary. The research was of quasi experimental design and was carried out with a sample of 19 students in the Control Group and 19 students in the Experimental Group from a national university in Peru. For data collection, a pre-test and a post-test were applied regarding the English-speaking competency, and a questionnaire of perception on the use of YouGlish was also used. The arithmetic mean indicates that it improved by 35.25 points using YouGlish when comparing the entrance and exit tests. Concluding with an increase in the English-Speaking competency among university students.